Effectiveness of a care bundle to reduce surgical site infections in patients having open colorectal surgery - Tanner, Judith; Kiernan, Martin; Hilliam, R.; Davey, S.; Collins, E.; Wood, T.; Ball, J.; Leaper, David (Royal College of Surgeons of England, 2016)
Introduction